Journal Club: Neurofilament Light Chain Levels in Anti-NMDAR Encephalitis and Primary Psychiatric Psychosis. (8th November 2022) - Deerhake, M. Elizabeth; Giarraputo, James; Gupta, Megha; Eckstein, Christopher
Abstract : Anti-NMDA receptor encephalitis (NMDARe) is an autoimmune brain disorder characterized by antibodies specific for the NMDA receptor in CSF. 1 A subset of patients with NMDARe present with isolated psychosis, 2 making it challenging to distinguish NMDARe from a primary psychiatric disorder without CSF antibody testing. Although CSF antibody testing is necessary for diagnosing NMDARe, complementary serum tests are needed, particularly in clinical settings where lumbar puncture is difficult to obtain.